2020
DOI: 10.1177/1756286420951072
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes after exposure to interferon beta: a register-based cohort study among women with MS in Finland and Sweden

Abstract: Background Our aim was to estimate and compare the prevalence of adverse pregnancy outcomes among pregnant women with multiple sclerosis (MS) exposed to interferon beta (IFNB) and among women with MS unexposed to any MS disease-modifying drug (MSDMD). Methods This cohort study used Finnish (1996–2014) and Swedish (2005–2014) national register data. Women with MS having IFNB dispensed 6 months before or during pregnancy as the only medication were considered as IFNB exposed (only IFNB-exposed), whereas women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 25 publications
6
32
0
1
Order By: Relevance
“…After stratification by newborn characteristics, our results were also consistent with the unstratified results in the same population [31], with no increased prevalence estimates among the exposed pregnancies. Although newborns born within 28-36 weeks of gestation had a numerically higher prevalence of MCAs and the composite serious adverse pregnancy outcomes in the IFN-beta exposed pregnancies, the result was based on few outcomes per stratum and the precision of the prevalence was low.…”
Section: Newborn Characteristicssupporting
confidence: 89%
See 4 more Smart Citations
“…After stratification by newborn characteristics, our results were also consistent with the unstratified results in the same population [31], with no increased prevalence estimates among the exposed pregnancies. Although newborns born within 28-36 weeks of gestation had a numerically higher prevalence of MCAs and the composite serious adverse pregnancy outcomes in the IFN-beta exposed pregnancies, the result was based on few outcomes per stratum and the precision of the prevalence was low.…”
Section: Newborn Characteristicssupporting
confidence: 89%
“…Our result indicated that the descriptive prevalence of serious and other adverse pregnancy outcomes was not increased among pregnancies exposed to IFN-beta in the strata of maternal characteristics, which is consistent with the unstratified results in the same population [19,31]. The finding that in some strata the prevalence appeared decreased among the pregnancies exposed only to IFN-beta compared to pregnancies unexposed to any MSDMDs, without statistical significance, may have been caused by underlying factors that were unfavourable among the unexposed women and that this study using the available register data could not detect (e.g., life-style factors (beyond BMI), maternal alcohol and substance use, or actual use of teratogenic drugs before and during pregnancy).…”
Section: Maternal Characteristicssupporting
confidence: 87%
See 3 more Smart Citations